Thursday

April 24, 2014

April 24, 2014

Posted by **Candice** on Monday, October 22, 2012 at 9:20pm.

ThankS!

- Math -
**Steve**, Tuesday, October 23, 2012 at 5:18amcheck for n=1

2^3 - 3^1 = 8-3 = 5

assume for k:

2^(3k) - 3^k = 5m for some m

now plug in k+1

2^(3(k+1)) - 3^(k+1)

= 2^(3k+3) - 3^(k+1)

= 2^3 * 2^(2k) - 3*3^k

= 8*2^(3k) - 3*3^k

= 3*2^(3k) + 5*2^(3k) - 3*3^k

= 3(2^(3k) - 3^k) + 5*2^(3k)

= 3(5m) + 5*2^(3k)

which is a multiple of 5.

**Related Questions**

math - Prove by mathematical induction that : E (3r-5)= 3n^2-7n /2 r=1

Algebra - Prove by mathematical induction that 3^(3n+1) + 2^(n+1) is divisible ...

math - use mathematical induction to prove -1/2^n = 1/2^n - 1

Calculus - Use mathematical induction to prove that the statement holds for all ...

Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...

AP Calc - Use mathematical induction to prove that the statement holds for all ...

math - *if it is in parentheses, it is subscripted. the sequence {a(n)} is ...

Pre-cal - use mathematical induction to prove that 1^2 + 2^2 + 3^2 + ... + n^2...

Calculus - Use mathematical induction to prove that each proposition is valid ...

Mathematical induction. I'm stuck. So far I have.. - For all integers n ≥ ...